Major Label Mastering - Göknar, Evren (Focal Press, 2020)
Major Label Mastering: Professional Mastering Process distills 25 years of mastering experience at Capitol Records into practical understandings and reliable systems. Containing unparalleled insights, this book reveals the mastering tricks and techniques used by Evren Göknar at one of the world's most notable record labels. Beginning with the requisite competencies every Mastering Engineer must develop, Major Label Mastering delves into the particulars of the mastering studio, as well as fundamental mastering tools. Included among these tools is The Five Step Mastering Process, a rigorously tested system that equips the practitioner to successfully and confidently master a project to exacting standards of audio fidelity. Covering all bases, the book discusses both macro and micro considerations: from mindset approach and connecting with clients down to detailed guidelines for processing audio, advanced methods, and audio restoration. Each chapter ends with exercises intended to deepen understanding and skill, or to supplement course study. Suitable for all levels, this is a unique resource for students, artists, and recording and Mastering Engineers alike. Major Label Mastering is supplemented by digital resources including audio examples and video tutorials.